A Viable Route for Lithium Ion Detection (Eur. J. Inorg. Chem. 3/2014). Issue 3 (January 2014) - Gulino, Antonino; Lupo, Fabio; Cristaldi, Domenico A.; Pappalardo, Sebastiano; Capici, Calogero; Gattuso, Giuseppe; Notti, Anna; Parisi, Melchiorre F.
Abstract : The cover picture shows sad and smiley faces sketched on the silica supports resting on the handle of the magnifying lens, which signal the penchant of a pyridylazocalix[4]arene‐immobilized monolayer (PyAzoC4‐IM) for lithium ions. This hybrid organic–inorganic device is able to selectively and reversibly sense lithium ions at ppm levels in the presence of competing cations. Upon recognition, the PyAzoC4‐IM "blushes", turning into a shade of pink that allows naked‐eye detection. The immobilized monolayer can be regenerated by simple rinsing in diluted hydrochloric acid. Details are discussed in the article by A. Gulino, M. F. Parisi et al. onp. 442 ff . For more on the story behind the cover research, see theCover Profile .